Glioblastoma Following Treated Medulloblastoma After 29 Years in the Posterior Fossa: Case Report and Review of Literature - Mesbahi, Tarek; Zaine, Hind; Mahazou Abdou, Ismaël; Chekrine, Tarik; Sahraoui, Souha; Karkouri, Mehdi; Lakhdar, Abdelhakim (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is a high-grade glioma that may be a rare complication of radiotherapy. We report a case of a patient who was treated for medulloblastoma (MB) of the posterior fossa at the age of 27 years. Twenty-nine years later, at the age of 56 years, he presented with a double-location tumor: supratentorial and in the posterior fossa. Imaging features of the supratentorial location were very suggestive of a meningioma. We operated on the posterior fossa location, which revealed a glioblastoma. Histologically, the tumor cells exhibited characteristics of both GBM and rhabdoid tumor cells. Literature reports of cases of GBM following MB at the same place are very rare, and presenting rhabdoid characteristics is even rarer. This is the first case of MB and GBM at ages 27 and 56 years, respectively. The double-location supratentorial probable meningioma and GBM of the posterior fossa 32 years after MB is the only case reported in the literature. What to do in this case remains a topic of debate, and there are no clear recommendations in the literature.